Rasgos de personalidad vulnerables al síndrome de Burnout en los choferes profesionales de la Cooperativa de Taxis Benjamín Carrión durante el periodo diciembre 2014-abril 2015 - Sigüenza Galarza, Alexis Fabricio (2015)
Burnout's Syndrome is one of five more serious sanitary problems of the current importance, so much for his discharge prevalence in the professionals of different areas as: health, education, administration, etc., since for the possible consequences in the population represented by the above mentioned professionals. The cooperative of taxis Benjamin Carrión of Loja's City could not stay out of this reality. In the present investigation the vulnerability decided to suffer syndrome of burnout in the professional drivers; the features of personality were identified and which of the professionals are more inclined to suffer the above mentioned syndrome; finally a psico-educational offer of awareness was elaborated to the drivers focused on the reasons and consequences of this syndrome. The investigation was of transverse descriptive type with mixed approach, with a cuanti-qualitative paradigm of investigation. In the field investigation Benjamin Carrión applied the Test MCMI-III and Maslach's Test to 53 drivers of the cooperative of taxis, in which it was possible to demonstrate that the most common features of personality in the drivers are of type schizoid and narcissist; that the participants possess 41 % of high risk of suffering the syndrome, 55 % of moderate risk and 4 % of low risk. It is for this that, focused in the results we conclude that the reasons of the syndrome are multifactoriales, by which there is recommended an intervention directed to the needs of the cooperative. KEY WORDS: Features of Personality, vulnerability, Burnout's Syndrome, offer psychoeducational, transverse descriptive